EVALUASI EFISIENSI TATA RUANG SEKOLAH MINGGU ANAK DI GKI SUNTER SEBAGAI SARANA EDUKASI DAN SOSIAL - Laura Tri Agustin; Jason Christian Adam; Johanna Teresa Verisya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2026)
Early childhood education, encompassing both formal and informal settings such as Sunday schools, plays a crucial role in shaping quality individuals. An ergonomic learning environment is paramount for educational effectiveness and the holistic development of children's potential. This study addresses the challenge of enhancing the ergonomic comfort of Sunday school classrooms at Gereja Kristen Indonesia (GKI) Sunter, North Jakarta, particularly in the context of participant density and spatial limitations. The research aimed to (1) identify the current ergonomic comfort level of existing classrooms and (2) propose functional and safe spatial layouts for children. A participatory and evaluative approach was employed through three stages: data collection and field survey, problem mapping and analysis, and solution design and proposal. Survey findings revealed that fluctuating participant numbers posed a significant challenge to spatial arrangement. Based on this analysis, three alternative classroom layouts were developed, tailored to participant capacity and activity types: a